Memperkuat Loyalitas Karyawan di Era Digital: Peran Kepemimpinan Digital, Budaya Kaizen, Kompensasi, dan Perilaku Kerja Inovatif - Fahrurrozi, Muhammad Anis; Arief, Muhtosim; Irma, Dasih (Lembaga Penelitian Universitas YARSI, 2026)
This study investigates the effects of digital leadership, Kaizen culture, and employee compensation on employee loyalty, with innovative work behavior (IWB) as a mediating variable. The research adopts a quantitative approach and was conducted in an energy infrastructure company using data collected from 102 employees through structured questionnaires. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that employee compensation has a significant positive effect on innovative work behavior and employee loyalty, while innovative work behavior also significantly predicts employee loyalty. In contrast, digital leadership and Kaizen culture do not show significant direct effects on either innovative work behavior or employee loyalty. Mediation analysis reveals that innovative work behavior significantly mediates the relationship between employee compensation and employee loyalty, but does not mediate the effects of digital leadership and Kaizen culture. The structural model demonstrates substantial explanatory power, with R² values of 0.518 for innovative work behavior and 0.636 for employee loyalty, indicating that the proposed variables explain a meaningful proportion of variance in the endogenous constructs. These findings suggest that compensation is the most influential driver of employee loyalty, both directly and indirectly through innovative behavior. Practically, the study emphasizes fair compensation for loyalty.